The Influence of Work Discipline and Work Motivation on Employee Work Productivity (Study at UD. Primacon Paving) - Dimas Eka Prasetiyo; Deni Widyo Prasetyo (Journal of International Accounting, Taxation and Information Systems, 2024)
The main objective of this study is to examine how work discipline and motivation affect the work productivity of production employees at UD. Primacon Paving. An explanatory research approach is employed, involving field data collection.   The target population consists of 47 employees working in the production department at UD. Primacon Paving Kepuh Kembeng. The researchers utilised multiple Linear Regression statistical methods and hypothesis testing to analyse the data, as well as the coefficient of determination.   The study findings suggest that maintaining good work discipline can positively influence the work productivity of employees at UD. Primacon Paving Kembeng, while high levels of work motivation can lead to increased Employee Work Productivity at UD. Primacon Paving Kembeng.